Insights Into Forensic Features and Genetic Structures of Guangdong Maoming Han Based on 27 Y-STRs - Fan, Haoliang; Xie, Qiqian; Li, Yanning; Wang, Lingxiang; Wen, Shao-Qing; Qiu, Pingming (Frontiers in Genetics, 2021)
Maoming is located in the southwest region of Guangdong Province and is the cradle of Gaoliang culture, which is the representative branch of Lingnan cultures. Historical records showed that the amalgamations between Gaoliang aborigines and distinct ethnic minorities had some influences on the shaping of Gaoliang culture, especially for the local Tai-kadai language-speaking Baiyue and Han Chinese from Central China. However, there is still no exact genetic evidence for the influences on the genetic pool of Maoming Han, and the genetic relationships between Maoming Han and other Chinese populations are still unclear. Hence, in order to get a better understanding of the paternal genetic structures and characterize the forensic features of 27 Y-chromosomal short tandem repeats (Y-STRs) in Han Chinese from Guangdong Maoming, we firstly applied the AmpFLSTR® Yfiler® Plus PCR Amplification Kit (Thermo Fisher Scientific, Waltham, MA, United States) to genotype the haplotypes in 431 Han males residing in Maoming. A total of 263 different alleles were determined across all 27 Y-STRs with the corresponding allelic frequencies from 0.0004 to 0.7401, and the range of genetic diversity (GD) was 0.4027 (DYS391) to 0.9596 (DYS385a/b). In the first batch of 27 Yfiler data in Maoming Han, 417 distinct haplotypes were discovered, and nine off-ladder alleles were identified at six Y-STRs; in addition, no copy number variant or null allele was detected. The overall haplotype diversity (HD) and discrimination capacity (DC) of 27 Yfiler were 0.9997 and 0.9675, respectively, which demonstrated that the 6-dye and 27-plex system has sufficient system effectiveness for forensic applications in Maoming Han. What is more, the phylogenetic analyses indicated that Maoming Han, which is a Southern Han Chinese population, has a close relationship with Meizhou Kejia, which uncovered that the role of the gene flows from surrounding Han populations in shaping the genetic pool of Maoming Han cannot be ignored. From the perspectives of genetics, linguistics, and geographies, the genetic structures of Han populations correspond to the patterns of the geographical-scale spatial distributions and the relationships of language families. Nevertheless, no exact genetic evidence supports the intimate relationships between Maoming Han and Tai-Kadai language-speaking populations and Han populations of Central Plains in the present study.